2007
DOI: 10.1556/jep.2007.1012
|View full text |Cite
|
Sign up to set email alerts
|

Perceived vulnerability to disease is positively related to the strength of preferences for apparent health in faces

Abstract: Abstract:People who are particularly vulnerable to disease may reduce their likelihood of contracting illnesses during social interactions by having particularly strong aversions to individuals who appear ill. Consistent with this proposal, here we show that men and women who perceive themselves to be particularly vulnerable to disease have stronger preferences for apparent health in dynamic faces than individuals who perceive themselves to be relatively less vulnerable to disease. This relationship was indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 22 publications
4
30
0
1
Order By: Relevance
“…Investigating how perceptions of pathogens and/or violence predict systematic variation in mate preferences among individual women within a given region or culture may also provide insight into these issues (e.g. [3,4]). Indeed, a recent study [5] demonstrated that women's preferences for masculinity in male faces, but not female faces, increased after viewing images with pathogen cues, but did not change after viewing matched images without pathogen cues.…”
mentioning
confidence: 99%
“…Investigating how perceptions of pathogens and/or violence predict systematic variation in mate preferences among individual women within a given region or culture may also provide insight into these issues (e.g. [3,4]). Indeed, a recent study [5] demonstrated that women's preferences for masculinity in male faces, but not female faces, increased after viewing images with pathogen cues, but did not change after viewing matched images without pathogen cues.…”
mentioning
confidence: 99%
“…Another limitation of the current study is that recent research has shown that an individual's perceived vulnerability to disease can affect their facial preferences. It has been shown that an individual will prefer healthy traits in a face if they believe they are more vulnerable to disease (Welling, Conway, DeBruine, and Jones 2007). Because of this fact, perceived vulnerability to disease measurements should be taken of each participant in future research.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to an emotional level that perception activates a negative evaluation of the infected individuals [2]. For example, individuals with birth marks in their faces [3] or with different types of physical disabilities are usually judged very negatively by ''healthy'' people, even knowing that those individuals are not carriers of an infectious disease [4]. This is especially notorious among people with a high-perceived vulnerability to disease.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a feeling related to the fact that obesity may be transmitted through contact with individuals that have weight problems has been reported [8]. If the mechanism that allows humans to detect pathogenic elements reacts with other type of physical diversions (such as facial marks [3] or disability [4]), in this case obesity could be also related to perceived vulnerability to disease. For example, it has been found that people who are more worried about infectious illnesses have worse antifat attitudes than those individuals that are not concerned about this type of diseases [9].…”
Section: Introductionmentioning
confidence: 99%